The anodic behaviour of nickel in molten sodium-nitrate-potassium-nitrate eutectic - Arvia, Alejandro Jorge (1972)
The kinetic behaviour of nickel anodes immersed in molten sodium-nitrate-potassium-nitrate eutectic has been investigated in the temperature range 244-314°C with steady and non-steady electrochemical methods. The metal passivates by formation of a NiO layer of an average thickness 11 A. A characteristic passivation potential is established, probably associated to a mixed potential, the over-all reaction being 2(Na, K)NO3 + Ni = NiO + 2NO2 + (Na, K)2O. Beyond the passivity region the dissolution of the passive film occurs, at an anode potential where both NOI- and oxide ions are able to discharge. The likely over-all electrochemical processes are envisaged with the aid of potential/p04- diagrams. The considerably changing electrode roughness make a mechanistic interpretation of the anodic processes very uncertain at present.